1998
DOI: 10.1103/physrevb.58.293
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic spin dynamics from spin-density-functional theory: Application to Fe, Co, and Ni

Abstract: The adiabatic theory of spin-density waves is developed on the basis of spin-density-functional theory. The wave-number-dependent exchange constant matrix is obtained from spin-density-functional calculations with constrained moment directions. The central assumption considers a fast electronic and a slow magnetic time scale, and postulates negligible correlation of the fast motion between different ionic sites. The parameter-free calculated magnon spectra for Fe, Co, and Ni are in excellent agreement with ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
253
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(277 citation statements)
references
References 40 publications
22
253
2
Order By: Relevance
“…In structure inverse methods one extracts the parameters for the Heisenberg model from the total energies of a set of magnetic structures. The structures used in this set are most often spin spirals, and there has been some debate as to whether small θ spin spiral or planar spin spiral structures should be used 2,3 . The alternative perturbative approach comes from considering the rotation of a pair of spins in some reference state by opposite and vanishing angles.…”
Section: Introductionmentioning
confidence: 99%
“…In structure inverse methods one extracts the parameters for the Heisenberg model from the total energies of a set of magnetic structures. The structures used in this set are most often spin spirals, and there has been some debate as to whether small θ spin spiral or planar spin spiral structures should be used 2,3 . The alternative perturbative approach comes from considering the rotation of a pair of spins in some reference state by opposite and vanishing angles.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the problem of adiabaticity in itinerant ferromagnets can be found in Ref. [52]. We have assumed here that the fundamental postulate of their theory holds, i.e., a much faster timescale of the electronic degrees of freedom with respect to the slow magnetic system, and further postulate that correlations of the fast ionic motion are negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Halilov at. al 36,37 have studied adiabatic spin waves computed using a frozen magnon method. This is analogous to the frozen phonon method where atoms are displaced from their equilibrium positions and the total energy is restored as a function of these positions.…”
Section: Figmentioning
confidence: 99%